2008
DOI: 10.1136/gut.2007.147496
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling protein-2 (UCP2) induces mitochondrial proton leak and increases susceptibility of non-alcoholic steatohepatitis (NASH) liver to ischaemia-reperfusion injury

Abstract: Upregulation of UCP2 in human and rat NASH liver induces mitochondrial uncoupling, lowers the redox pressure on the mitochondrial respiratory chain and acts as a protective mechanism against damage progression but compromises the liver capacity to respond to additional acute energy demands, such as ischaemia-reperfusion. These findings suggest that UCP2-dependent mitochondria uncoupling is an important factor underlying events leading to NASH and cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
187
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(198 citation statements)
references
References 47 publications
8
187
0
1
Order By: Relevance
“…The initiation and perpetuation of cell injury in NAFLD is associated with the increase of free radicals and the depletion of endogenous anti-oxidant defense both in human and rodents [26,27]. Several data suggest that lipotoxicity plays a crucial role also in the pathogenesis of cardiomyopathy underlying nonischemic chronic heart failure, a leading cause of death in patients with obesity and/or diabetes [9,16].…”
Section: Discussionmentioning
confidence: 99%
“…The initiation and perpetuation of cell injury in NAFLD is associated with the increase of free radicals and the depletion of endogenous anti-oxidant defense both in human and rodents [26,27]. Several data suggest that lipotoxicity plays a crucial role also in the pathogenesis of cardiomyopathy underlying nonischemic chronic heart failure, a leading cause of death in patients with obesity and/or diabetes [9,16].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this outcome, previous studies reported the depletion of this pool of GSH during hepatic I/R damage, and its restoration by GSH ethyl ester [37] or SAM [38] protected steatotic livers against I/R damage. Although this concept remains to be tested in human fatty liver, mitochondrial GSH depletion has been shown in nonalcoholic steatohepatitis [39] which is associated with increased free cholesterol accumulation and StAR overexpression [40]. If confirmed the role of …”
Section: Jhepat-d-10-00907-r Llacuna Et Al 18mentioning
confidence: 98%
“…29 Oxidative stress is mirrored by the increase of lipid peroxidation products (ie, malondialdehyde and hydroxynonenal) in patients with NASH and in animal models. [30][31][32] The importance of oxidative stress in the pathogenesis of steatohepatitis is underscored by the use of several antioxidants, associated with variable success, in patients with NASH; 33 a recent randomized controlled trial showed the efficacy of vitamin E in counteracting liver injury progression. 34 There is evidence that both ROS and RNS contribute to hepatocyte damage and inflammatory/fibrogenic cells activation.…”
Section: Discussionmentioning
confidence: 99%